Adjustment to Cancer among Patients with Breast Cancer Hospitalized in the Day Care Oncology Ward - Bąk, Ewelina; Waszut, Anna (Journal of Education, Health and Sport, 2018)
Introduction: Breast cancer is one of the most common malignant tumours affecting women. The treatment often involves the surgical removal of the neoplastic lesion or even the resection of the whole breast. The disease affects virtually every sphere of a woman's life. The aim of the work was to learn strategies for coping with pain on the example of patients of the Neurological Hospital of the City Hospital named after John Paul II in Bielsko-Biała.Materials and methods: The study involved 100 patients with breast cancer following oncological surgery who were hospitalized in the oncology ward of the Beskid Oncology Centre of the Town Hospital in Bielsko-Biała. The research was carried out from March to December 2017. The following research tools were used: self-inquiry questionnaire and the Mini-Mac Mental Adjustment Scale for cancer. Findings: While analysing the ways of coping with cancer, it was shown that the constructive style definitely dominates along with the high intensity of the positive re-evaluation strategy, the fighting spirit. The destructive style, however, scored low among the respondents. Conclusions: The patients showed an attitude leaning towards cancer adjustment. Most women had a positive attitude towards their disease.